Polygonatum sibiricum polysaccharides enhance pancreatic β-cell function in diabetic zebrafish by mitigating mitochondrial oxidative damage via the AMPK-SIRT1 pathway - Lin, Fan; Yu, Wenjing; Li, Ping; Tang, Shuyao; Ouyang, Yitong; Huang, Liya; Wu, Di; Cheng, Shaowu; Song, Zhenyan (Frontiers in Nutrition, 2025)
BackgroundMitochondrial oxidative damage in pancreatic β-cells is a key contributor to diabetes pathogenesis, particularly under hyperglycemic conditions. Polygonatum sibiricum polysaccharides (PSP) have demonstrated potential anti-diabetic effects; however, their precise mechanism, particularly through the AMPK-SIRT1 pathway, remains unclear.MethodsA diabetic zebrafish model was established by exposure to 2% glucose for 28 days. Zebrafish were divided into control, model, low-dose PSP (50 μg/mL), medium-dose PSP (100 μg/mL), high-dose PSP (200 μg/mL), and metformin groups. Behavioral, biochemical, and molecular analyses were performed to assess β-cell function, mitochondrial oxidative damage, and inflammation. Network pharmacology analysis was used to predict PSP targets, and molecular docking validated key protein interactions. Immunofluorescence and Western blotting (WB) were conducted to examine apoptosis-related protein expression.ResultsPolygonatum sibiricum polysaccharides significantly improved zebrafish swimming behavior, reduced blood glucose and fructosamine levels, and enhanced ATP production (p < 0.01). Antioxidant enzyme activities (SOD, CAT) increased, while oxidative stress markers (MDA) and inflammatory cytokines (IL-1β, IL-6, TNF-α) decreased (p < 0.01). PSP treatment downregulated Cycs expression, alleviating mitochondrial damage. Moreover, PSP upregulated AMPK and SIRT1 expression (p < 0.01), along with downstream regulators PGC-1α and Nrf1/2 (p < 0.01), confirming AMPK-SIRT1 pathway activation. Network pharmacology identified 389 shared targets between PSP and diabetes-related pathways, implicating key mechanisms of inflammation, insulin resistance, and mitochondrial dysfunction. Molecular docking demonstrated strong PSP binding affinities to AMPK and SIRT1. Immunofluorescence and WB analyses showed reduced cleaved caspase-3 levels and apoptosis in pancreatic β-cells following PSP treatment (p < 0.01).ConclusionPolygonatum sibiricum polysaccharides protects pancreatic β-cell function in diabetic zebrafish by mitigating mitochondrial oxidative stress and apoptosis via AMPK-SIRT1 pathway activation. Network pharmacology and molecular docking further highlight PSP’s potential as a multi-target therapeutic agent for diabetes.